Modelling in Searching the Profitable Decisions - Simanauskas, Leonas (Ekonomika, 1998)
The object of our study is the management decisions making process. The aim is to discuss from both the theoretical and the practical viewpoint the problems of description the process of the enerprices planing and management decisions making procedures.The modelling technology for evaluation the quality of management from the perspective of managers are discussed. Some formal methods and models for evaluation and selection of the best planing decisions are suggested. Construction models are based on the linear programming and multicriterian decision methods for selection the best decisions alternatives.Identification the needs and goals of managers involve analysis situations and the basic problems existing in the current environment and efforts to determine changes in the environment which could help make the most profitabily decisionsFor evaluation and selecting of the best planing decision it is critical to find the best solution.The next tasks includes the project decisions alternatives evaluation and selection.The modelling technology include the sensivity analysis. These models are realised and use in practice to analyse and planing.